1975
DOI: 10.1073/pnas.72.4.1612
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationship between immunoglobulins and transplantation antigens.

Abstract: The major human and murine histocompatibility antigens are tetrameric molecules with an apparent molecular weight of about 130,000. They are composed of two types of polypeptide chains. The two light chains, previously identified as 6B2-microglobulins, are bound to the two heavy, alloantigenic HL-A or H-2 polypeptide chains by noncovalent interactions only. The heavy chains are held together by disulfide bridge(s) located in the part of the molecule that is attached to the cell membrane.By limited proteolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
64
0

Year Published

1975
1975
1981
1981

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 34 publications
11
64
0
Order By: Relevance
“…3A (34,35), surface immunoglobulins (36,37), and oncornavirus glycoproteins (38). Ando and Steiner (25) reported evidence for intramolecular disulfide bonds in platelet membranes but found no intermolecular bonds.…”
Section: Extraction Of Surface Proteins Is Promoted By Reducingmentioning
confidence: 99%
“…3A (34,35), surface immunoglobulins (36,37), and oncornavirus glycoproteins (38). Ando and Steiner (25) reported evidence for intramolecular disulfide bonds in platelet membranes but found no intermolecular bonds.…”
Section: Extraction Of Surface Proteins Is Promoted By Reducingmentioning
confidence: 99%
“…Indeed, the V (variable) and C (constant) regions of immunoglobulins demonstrate no primary sequence homologies, but they have very similar three-dimensional structures. In this regard, if the transplantation antigens actually turn out to consist of "heavy" (45,000 dalton) and "light" (12,000 dalton) chains (17) that fold into immunoglobulin-like domains (25), perhaps the contact residues between the two chains would be structurally homologous to their immunoglobulin counterparts from the VL and VH doThis simple calculation assumes that any of the twenty different amino acids are equally likely to appear at any of the residue positions. Hence the probability that any two random sequences are as closely related as indicated in Fig.…”
Section: )mentioning
confidence: 99%
“…We have recently suggested that alleles (or allotypes) can be divided into two categories (27). Alternative forms of simple allotypes segregate in a Mendelian fashion in mating studies and differ by one or a few amino-acid substitutions [e.g., the Inv marker of the human K chain (25)]. In contrast, alternative forms of complex allotypes differ by multiple amino-acid residues and generally segregate in a Mendelian fashion [e.g., the group a and group b allotypes of the rabbit (see ref.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The larger component carries the serologically identified alloantigenic determinants (5). Although at least 40 different antisera are required to define the varying specificities of the HLA antigens, accumulating evidence from several sources has suggested that a rather limited degree of chemical heterogeneity may actually be present (6)(7)(8). This investigation was undertaken to compare HLA antigens of different specificities, using a newly devised method for the chemical analysis of microgram amounts of lactoperoxidase radioiodinated cell surface antigens.…”
mentioning
confidence: 99%